Looking for Moderate Fiqh: The Thought of Mohammad Hashim Kamali on the Reformation of Rigidity and Inflexibility in Islamic Law - Hefni, Wildani; Mustofa, Imam; Ahmadi, Rizqa (AL-ISTINBATH : Jurnal Hukum Islam, 2025)
This article aims to examine Mohammad Hashim Kamali’s thoughts on the paradigm of moderate Islamic law (wasatiyyah), which emphasizes harmonious values and a humanistic approach as an integral part of maqasid al-shariah. The focus is on how Kamali’s moderate fiqh can address contemporary issues and offer an alternative to rigid, literal interpretations of Islamic law. This research employs a library research method, analyzing Kamali’s works and relevant literature to explore the foundations of his thought. A philosophical-normative analysis is used to discuss how Kamali’s ideas on moderate fiqh are rooted in the objectives of Islamic law (maqasid al-shariah) and how they align with contemporary needs for flexibility and human-centered legal reasoning. The study finds that Kamali proposes a reformation of Islamic law in response to the violence and rigidity fostered by formalistic legal understandings. His moderate fiqh, based on the principles of wasatiyyah, advocates for a balanced, context-sensitive approach to Islamic law that aligns with humanist values and social justice, all while upholding the core objectives of maqasid al-shariah. Kamali’s thought offers a significant contribution to the development of Islamic jurisprudence, proposing a moderate and adaptive legal framework that remains faithful to Islamic principles while responding to the complexities of the modern world. His approach can help reconcile traditional Islamic law with contemporary humanistic values, promoting peace, justice, and tolerance.